Comparative study phytochemical and antioxidant activity of the epicarpia of the hawaiian and tainung variety (carica papaya) - Corozo Marquez, Jennifer Anthonella; Zuñiga Tapia, Ahsly Briggitte (Revista Universidad de Guayaquil, 2021)
The Carica papaya peel generates waste that becomes environmental pollution which affects the population. A Hawaiian papaya has a weight of 453.6 grams, the peel of this fruit weighs 56.67 grams which represents 30% of waste; As for the Tainung variety, a mature fruit has an average weight of 1814.37 grams, the peel of this fruit weighs 198.447 grams, which represents 40% of waste. Situation that merits a study of the chemical composition and the therapeutic activities that they could represent. The imbalance between antioxidant activity and free radicals is related to oxidative stress; therefore, the consumption of fruits and vegetables provide important antioxidants for the body. This titration work aims to determine the secondary metabolites and the antioxidant activity of the epicarp of Carica papaya, Hawaiian and Tainung by preliminary phytochemical screening and spectrophotometric method. For which the secondary metabolites were determined and the Tainung variety presented alkaloids, phenols, flavonoids and saponins and the Hawaiian variety alkaloids, phenols, flavonoidsand saponins, then the total polyphenols were quantified by the Folin Ciocalteu method, the Tainung variety gave as a result 0.86% and the Hawaiian variety gave 0.70%. The antioxidant activity was determined by the DPPH method where the tainung variety gave the result IC 50 (Gallic Ac.) 137.86 mg / ml - IC 50 (Ascorbic Ac.) 22.24 mg / ml and the Hawaiian variety presented IC 50 (Ac. Gallic) 130.20 mg / ml - IC 50 (Ascorbic Acid) 21.00mg / ml.
Keywords: Carica Papaya; Antioxidant activity; Total polyphenols